Synthesis, Photophysical and Supramolecular Properties of a π-Conjugated Molecular Crown Containing a Pentagonal Unit: A Model Compound for Fullerene C240 - Huang, Qiang; Wu, Yayu; Zhou, Yu; Liu, Huiqing; Wang, Jinyi; Wang, Shengda; Du, Pingwu (Synthesis, 2020)
The total synthesis of carbon onions is a significant challenge in the fields of materials science and organic chemistry. To date, the synthesis of even a fragment of fullerene C240 and its smallest carbon onion C60@C240 remains poorly explored. Herein, we demonstrate a bottom-up strategy to produce a novel π-extended molecular crown-shaped molecule (MC3) containing curved pentagonal and hexagonal units. This molecular crown represents a curved model compound for fullerene C240 and is fully characterized by NMR, mass spectrometry, UV-vis absorption, and from its emission spectra. Its supramolecular host–guest interaction with fullerene C60 is also investigated. MC3 and C60@MC3 can potentially be employed as seeds or templates for the bottom-up synthesis of fullerene C240 and the carbon onion C60@C240, respectively.
Keywords: carbon onion; fullerenes; macrocycles; bottom-up synthesis; supramolecular chemistry